EFEKTIFITAS KONSELING KELOMPOK DENGAN RELAXATION TECHNIQUE (TEKNIK RELAKSASI) UNTUK MEREDUKSI MOOD SWINGS (PERUBAHAN SUASANA HATI) BELAJAR SISWA KELAS XL F-2 BOARDING SCHOOL MAN 1 SURAKARTA TAHUN AJARAN 2025/2026 - Zahratul Firdausi, Yasmin; Adi Putro, Eko; Jawandi, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of group counseling services using relaxation techniques in reducing mood swings in learning among students of class XI F-2 Boarding School at MAN 1 Surakarta in the 2025/2026 academic year. The study employed a quantitative approach with a pre-experimental design using a One Group Pretest-Posttest Design. The research subjects consisted of 10 students of class XI F-2 Boarding School at MAN 1 Surakarta selected through purposive sampling. The research instrument was a mood swings questionnaire that had been tested for validity and reliability. Data analysis was conducted using the Wilcoxon test with the assistance of SPSS version 23.The results showed a decrease in mood swings scores after the implementation of group counseling with relaxation techniques, with a mean pre-test score of 106.3 and a mean post-test score of 91.9. The Wilcoxon test results indicated a significance value of 0.005 < 0.05, thus it can be concluded that group counseling services using relaxation techniques are effective in reducing learning-related mood swings among students of class XI F-2 Boarding School at MAN 1 Surakarta. This study implies that the application of relaxation techniques in group counseling can help students regulate emotions, calm their thoughts, and improve learning concentration.